EFFECT OF DIFFERENT DIETARY PROTEIN LEVELS OF CYCLOPEEZE MEAL ON GROWTH, SURVIVAL AND CARCASS COMPOSITION OF LITOPENAEUS VANNAMEI (BOONE, 1931) - PRAKASH, CH.BHANU; D. R. K. REDDY; T. K. GHOSH; RAJAK, ALOK; D. RAMALINGAIAH (The Bioscan, 2014)
Present study was undertaken to study Cyclop-eeze (CE) meal of different protein levels (25%, 30% and 35%) were used in the experiment. The experiments were conducted for 56 days in aquaria. Triplicates were maintained for each of the treatment. Feed was given 3 times a day @ 5% of body weight. The growth performance of L. vannamei was found to be best when fed with diet CE30 (7.75gm). Specific growth rate was highest (1.863) in shrimps fed with diet CE30. Survival rates were best in shrimps fed on CE30, which showed 75% and FCR of 3.34. Carcass composition of L. vannamei showed the highest protein content in shrimps fed with CE30 diet (74.4%). Highest ether extract (2.5%) and crude fibre content (4.6%) was recorded. Ash content was high in shrimps fed with CE35 diet (9.3%). The present study suggests that, during the juvenile stages of L. vannamei culture use of Cyclop-eeze meal improved the survival rate, showing good growth, with less FCR.